PENYULUHAN TENTANG DUKUNGAN SUAMI PADA MASA NIFAS UNTUK MENCEGAH POST PARTUM BLUES - Arie Anggraini; Eka Rahmawati; Reffi Dhamayanti; Ahmad Arif (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2024)
According to WHO, the problem of postpartum blues is experienced by postpartum mothers, namely 300-750 per 1000 postpartum mothers in the world (World Health Organization, 2017). Meanwhile, in Asia, the incidence of post partum blues varies from 26% - 85%. Overall, 20% of postpartum mothers experience post partum blues (Siallagan et al., 2022). Indonesia as a developing country has a figure ranging between 50-70% of the incidence of post partum blues (Samria & Indah Haerunnisa, 2021). If this problem is not paid attention to, post partum blues will continue to develop and endanger many postpartum mothers. Husband's support plays a very important role during the postpartum period. This is because the husband is someone who is able to provide a sense of security and comfort to the postpartum mother, and is the closest person to the postpartum mother. If the husband is able to provide a sense of security and comfort then difficulties for postpartum mothers can be minimized (Ariani et al., 2022)